Labor Market Outcomes of Highly Educated Immigrants: Does Your Name Matter? - Dafeng Xu (European Regional Science Association (ERSA), 2015)
Prior empirical research shows that acculturation in the host country might be positively related to immigrants? labor market outcomes. However, whether acculturation helps highly educated immigrants in the labor market is in question, as they have completed a significant fraction of human capital accumulation in their home country. In this paper, I attempt to identify the effect of acculturation on labor market outcomes of Chinese students with bachelor?s degrees in Chinese colleges and graduate degrees in US schools. Acculturation is measured by the use of Westernized names on the online social networking site. Various statistical models show no evidence that the use of Westernized names has significant impacts on labor market outcomes.
Keywords: J1; J6; Z1; 330; acculturation; Westernized; name; labor; market; outcomes; immigration